Long‐Distance Mothering in Urban Kenya. Issue 2 (4th September 2020) - Cotton, Cassandra; Beguy, Donatien
Abstract: Objective: To explore the long‐distance mothering strategies of migrant women living in urban slums in Nairobi, Kenya. Background: Throughout sub‐Saharan Africa, migration has had a profound influence on family life. As women's migration increases, particularly to urban slums, mothers may choose to live apart from children, fostering them to kin. Though fostering is common in many African countries, the unique characteristics of separation due to maternal migration may result in development of long‐distance mothering strategies to maintain mother–child relationships over time and space. Method: Forty‐seven in‐depth interviews with mothers living in two Nairobi slums were analyzed to explore key strategies women use to maintain relationships with children who live elsewhere, examining the importance women place on sustaining relationships through financial and emotional support, and whether long‐distance mothering is sufficient. Results: Efforts to maintain mother–child relationships over time and space are integral to many migrant women's understanding of themselves as mothers. Commitments to provide financially, as well as frequent communication and visits to ensure emotional well‐being of children, are described as key strategies to sustain relationships, whether separations are short term or permanent. For many mothers, however, these long‐distance efforts are viewed as insufficient forms of mothering, even in a context where child fostering is relatively normalized. Conclusion: These long‐distance strategies may reflect a more nuanced approach to fostering or greater flexibility in fostering arrangements when mothers migrate, where frequent contact and financial support play an important role in maintaining mother–child relationships rather than shifting emotional and financial care to foster parents.